The sovereignty of God in salvation biblical essays - Ellis, E. Earle (Edward Earle) (London : T & T Clark, 2009)
In his new work The Sovereignty of God in Salvation E. Earle Ellis sets out to explore God's sovereign purpose both in individual salvation and in the salvation history within which the Bible has been authored, transmitted, interpreted and communicated. In the process he touches on such themes as the nature of free will; the manifestation God's sovereignty in the life and ministry of the Apostle Paul; the presence of God's hand in the transmission and interpretation of the biblical texts; and new perspectives on both the modern inclination to emphasise Paul's use of Graeco-Roman rhetoric as we
God's sovereign grace in salvation and the nature of man's free will -- Paul, predestined apostle of Christ Jesus : whence the name and the title? -- Colossians 1:12-20 : Christus creator, Christus salvator -- Perspectives on biblical interpretation -- Paul and Graeco-Roman rhetoric -- Dynamic equivalence theory, feminist ideology and three recent Bible versions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Providence and government of God; Religion; RELIGION -- Christian Theology -- General; Bibel; Barmherzigkeit Gottes; Gnade; 2; Wille Gottes; Rechtfertigungslehre; Heil; 2; Electronic books